Good Corporate Governance, Profitability and Institutional Ownership on Corporate Financial Performance Moderated by Dividend Policy - Azahra, Nurlisti; Lusiyanawati; Puriayu, Nanik Leanikha; Yulianto, Agung (Yayasan Ilomata, 2024)
The decline in financial performance in a company is often caused due to a weak corporate governance system. Therefore, this research aimed to assess the Implementation of Good Corporate Governance, Profitability and Institutional Ownership on Corporate Financial Performance with Dividend Policy as a Moderating Variable. This research was conducted over a 4-year period, namely 2019-2022. The research population consists of State-Owned Public Enterprise companies that are listed on the IDX during the period of 2019-2022. A sample of State-Owned Enterprises companies listed on the IDX that satisfy all the criteria for this research is selected using purposive sampling. The data analysis method used uses a panel data regression model to test the effect of each variable on the company's financial performance. The research findings show that, while profitability does influence the financial performance of a company, the presence of an audit committee, an independent board of commissioners, or institutional ownership does not have a significant impact. In addition, when adjusted for dividend policy, the influence of the audit committee, profitability, and institutional ownership on the financial performance of the company is not significant. Conversely, the dividend policy adhered to by the independent board of commissioners impacts the financial performance of the company. The implication of this study for State-Owned Enterprises can utilize this research to be wiser in choosing corporate governance policies that are in accordance with the company so that there is no decline in the company's financial performance.